2016
DOI: 10.3389/fpsyg.2016.02006
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Psychoeducation Program for Caregivers of First-Episode of Psychosis: An Experience of Chinese Population in Hong Kong

Abstract: Caregivers of patients with first-episode psychosis are often with little knowledge about the illness and experience more burden of care. Psychoeducation to caregivers has shown to be effective in improving outcomes of patients and possibly reduce stress of the caregivers. This has been recommended as one of the key psychosocial interventions for specific early intervention for psychosis service. However, the accessibility of the service, high case load of the health care professionals and self-stigma of careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 31 publications
(33 reference statements)
1
36
0
Order By: Relevance
“…[45][46][47]53 With exception of one study, the remainder were conducted in Hong Kong, 48 Ireland, 50 Turkey, 52 and the United Kingdom. 51 There was one study, Perron,49 where 26 of the 30 participants were recruited from the USA and the remaining sample had come from Peru, Australia, and Canada.…”
Section: Study Originmentioning
confidence: 99%
See 4 more Smart Citations
“…[45][46][47]53 With exception of one study, the remainder were conducted in Hong Kong, 48 Ireland, 50 Turkey, 52 and the United Kingdom. 51 There was one study, Perron,49 where 26 of the 30 participants were recruited from the USA and the remaining sample had come from Peru, Australia, and Canada.…”
Section: Study Originmentioning
confidence: 99%
“…The individual number of participants reported in each study ranged from n=16 47 to n=91. 48 Participants were predominately female in eight of the nine studies that provided gender data. 45,46,48,49,50,51,52,53 While more than half the studies employed carer only participants only, four papers reported data for carer participants and the individuals they provided informal care for.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations